Patrimônio nacional ambiental na Constituição Federal: o artigo 225 parágrafo 4º da Constituição Federal de 1988 e os possíveis motivos e consequências da ausência do Cerrado no rol de proteção - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The Brazilian Cerrado has an expressive territorial extension, is biodiverse, besides being a strategic region for agribusiness. Its occupation was intensified in a period in which agribusiness assumes great importance in the growth of the country. The promulgation of the Federal Constitution of 1988 brought a chapter dedicated to the environment but left the Cerrado off the list of biomes protected as national heritage. This fact can be observed by several aspects, including the economic issue and the political interests involved. The study aimed to understand the legal meaning of the term national heritage contained in article 225, paragraph 4 of the Federal Constitution and the reasons for the absence of the Cerrado in the list of the legal provision. In achieving the results, the Cerrado was characterized as a biome, territory and according to the concept of territory biome; the survey of the context of the wording of Art. 225 of the Federal Constitution, in particular with regard to Paragraph 4, which establishes the Brazilian Amazon Forest, the Atlantic Forest, the Serra do Mar, the Pantanal Mato-Grossense and the Coastal Zone as national heritage and is omitted in relation to the Cerrado; and the process of PEC 504/2010, which aims to include the Cerrado and Caatinga in that list. The results obtained point to the existence of symbolic and legal impacts from this non-insertion of the Cerrado in the list of national heritages. Thus, political and economic factors are presented as possible reasons for selective environmental protection.
Keywords: Meio ambiente; Biomas; Legislação ambiental; Environment; Biomes; SANEAMENTO AMBIENTAL::LEGISLACAO AMBIENTAL